PEMANFAATAN TANAMAN OBAT KELUARGA (TOGA) DAN PENYULUHAN PHBS SEBAGAI UPAYA PENINGKATAN KESEHATAN MASYARAKAT DI KELURAHAN KADIA KECAMATAN KADIA KOTA KENDARI - Jafriati Jafriati; Asnia Zainuddin; Nani Yuniar; Fifi Nirmala; Harleli Harleli; Syawal Kamiluddin Saptaputra (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2023)
Thematic Real Work Lecture (KKN) is a program held every year at Haluoleo Kendari University. One of the UHO Thematic KKN was held in Kadia Village, Kadia District, Kendari City with the title KKN "Utilization of Family Medicinal Plants (Toga) and PHBS Counseling as an Effort to Improve Public Health in Kadia Village, Kadia District, Kendari City". The purpose of this Thematic KKN is to explain the concepts, objectives, and processes as well as the expected outputs of the Thematic KKN with the theme Utilization of Family Medicinal Plants (Toga) and PHBS Counseling as an effort to improve public health in Kadia Village, Kadia District, Kendari City and provide practical knowledge and skills for stunting detection and determination of nutritional status through health education. The Thematic KKN work program is conducted offline, with the team being divided into several groups to complete the prepared work program. Initially, a survey is conducted to observe phenomena occurring in the field. This helps the team formulate solutions that later become the KKN activities' work program. With the successful completion of the Thematic KKN student work program in Kadia Village, Kadia District, Kendari City, the Tri Dharma of Higher Education can be properly elaborated to the community. Through the KKN-Thematic implementation, students can apply their gained knowledge during college in the form of community service in Kadia Village, Kadia District, Kendari City.